Total economic value of ecosystem services in Malaysia: a review - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Penerbit Universiti Malaysia Terengganu, 2019)
Southeast Asia contains the world’s third largest tropical forests, currently experiencing a high deforestation rate, thus highlighting the need for conservation efforts. The full potential of ecosystem services in tropical forests has never been completely quantified in economic or monetary terms. This potential value is accessible by extraction of readily available information in both market and non-market terms. As such, an economic valuation approach is capable to estimate the full range of an ecosystem services benefits provided by a tropical forest. This paper reviews the suitable indicators pertinent to a Total Economic Value (TEV) of tropical forests to propose a conceptual framework for the TEV of Tropical Forest in Southeast Asia. The failure to impute price on ecosystems services in tropical forests would result in a misguided policy and the society would be in detrimental as a result of misallocation of resources.